THE PREPOSITIONAL ERRORS IN STUDENTS’ WRITING - Setyaningrum, Riya Risqi; Fatmawaty, Riryn (IKIP Mataram, 2020)
One of the important things in writing is grammar. The grammatical errors in writing may or will distort and disturb the coherence of the piece of writing. A preposition is a part of grammar that important to connect one word to another. Some students ignore the preposition in the right way. So, this study is eager to analyze the errors in using preposition produced by the students' first semester of English Education Department at Unisla in academic years 2019/2020 that consist of 45 students. The study focuses on what kinds of prepositional errors that are usually produced and the types of errors in using preposition mostly produced. This study uses descriptive qualitative to describes the reasons for preposition errors occur by analyzing the students' writing. The result is the students' first semester still produces some errors in; omission, addition, misformation, and misordering. The types of error that produced by the students is misformation errors with percentage 44,93%. It means the teachers have to pay more attention to teaching prepositions.